School Principal’s Entrepreneurial Leadership in Managing Financial Resources - Mas, Sitti Roskina; Yusuf, Khadijah R.; Nawai, Fory Armin (Universitas Negeri Malang, 2021)
This study attempts to explain (1) the creativity of the principal affects human resources to explore school financial resources, (2) the invention of the principal drives human resources to explore school financial resources, and (3) the strategy of the principal to engage in raising funds with the group. This analysis uses a qualitative descriptive technique. The results showed the principal's creativity affects human resources to explore the school's integrated financial resources in subjects that can inspire students to think creatively, work hard, and enable students to be autonomous in identifying sources of funds to be used in different activities.